THE ROLE OF IBN SINA'S SPIRITUAL HERITAGE IN RAISING A PHILOSOPHICAL WORLD VIEW - Kalandarova Farida Azamatovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article states that Abu Ali ibn Sina was a famous encyclopedic scientist - naturalist, philosopher who made a great contribution to world culture. It is said that Ibn Sina left an indelible mark in the fields of philosophy and medicine. Ibn Sina encourages the study of science in great depth and comprehensiveness.